The effect of various chemical modifications on the physicomechanical properties of 3D bioprinted scaffolds for tissue engineering - Parak, Azraa (My University, 2020)
The realm of tissue engineering has been modernized by 3D bioprinting. The efficacy of 3D bioprinting is limited, however, by the lack of available biomaterials which fulfill all the criteria required to be printed adequately (bioinks) and still produce constructs that align themselves with necessary scaffold requirements for use are engineered tissue. Its efficacy is thus also limited - in terms of clinical applicability - by the suboptimal properties of printed constructs, when compared to their biological counterparts. This project aimed to overcome these challenges by conceptualizing post-processing of 3D bioprinted structures in the form of post-printing chemical modifications which have been proposed to alter the mechanical properties of already printed structures. This could potentially improve the applicability of already available bioinks which are ideal for 3D printing processes, but lack adequate mechanical properties. The resultant alteration of these mechanical properties improves upon the concept of ‘customizable scaffolds’ and would allow for tunable mechanical properties of already available bioinks and their subsequently printed constructs. This idea of customizable scaffolds would potentially combat the lack of ideal bioinks, as printable bioinks could now be tuned for a variety of clinical applications. We also assess the efficacy of a novel bioink combination in the printing process and quantify the properties of its printed construct. Poly (3-hydroxybutyric acid-co-3-hydroxyvaleric acid) (PHBV) was used in combination with Cellulose Acetate Phthalate (CAP) as a bioink. Propylene carbonate and glycerol were incorporated into the formulation and evaluated for their effects as plasticizers. We then evaluated the effects of chemical surface modifications - in the form of aminolysis and hydrolysis - on mechanical properties, in order to introduce a new concept of post-printing modification as a method of inducing and/or exploiting desirable properties in printed constructs. Characterization of the bioink as well as the scaffolds were undertaken via Fourier Transform Infrared Spectroscopy, Differential Scanning Calorimetry, Scanning Electron Microscopy, and biomechanical testing. In vivo studies were performed to assess the biocompatibility and biodegradation of the produced and modified scaffolds, as well as the tissue response to these scaffolds. The scaffold was successfully printed and characterized, with the addition of propylene carbonate improving the printing process and improving the Young’s modulus of the construct as well as its degradation behaviour, and with the chemical modifications successfully altering the mechanical properties of the scaffolds, thus proving that constructs can be tailored post-printing in order to alter various properties and subsequently improve the variability in potential clinical applications. This investigation ultimately highlighted the success of post-processing in the form of chemical modifications to alter mechanical properties of already printed constructs, as well as evaluated the success of PHBV/CAP as a novel bioink combination
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfillment of the requirements for the degree of Master of Pharmacy
Keywords: Tissue engineering; Three- dimensional printing